A comparative study on SIP and LIP with reference to Indian mutual fund industry using non-regression performance evaluation ratios and single factor CAPM model. Issue 7 (3rd October 2022) - Goswami, Ajay Kumar D.; Patni, Ity; Choubey, Somya; Gupta, Nishu
Abstract: Investment in mutual funds can be made either through Lump Sum Investment Plan (LIP) or through Systematic Investment Plan (SIP). This study is an attempt to spread awareness amongst public/investors regarding the various advantages of SIP investments. The comparison has been done between LIP : and SIP investment option on selected equity funds of 8 Indian AMCs for a period of 3 years. Selected risk-return non regression measures are applied to assess the performance of selected equity funds. Further MCDM technique is applied to rank the SIP investment options of equity funds based on their performance evaluation results.